Auxiliary ECR heating system for the gas dynamic trap - Shalashov, A.G.; Gospodchikov, E.D.; Smolyakova, O.B.; Bagryansky, P.A.; Malygin, V.I.; Thumm, M. (Вопросы атомной науки и техники, 2012)
Physics aspects of a new system for electron cyclotron resonance heating (ECRH) at the magnetic mirror device Gas Dynamic Trap (GDT, Budker Institute, Novosibirsk) are discussed. This system based on two 400 kW / 54.5 GHz gyrotrons is aimed at increasing the electron temperature up to the range 250…350 eV for improved confinement. The key issue of the GDT conditions is that conventional ECRH geometries are not accessible. The proposed solution is based on a peculiar effect of radiation trapping in inhomogeneous magnetized plasma. Under specific conditions oblique launch of gyrotron radiation results in right-hand-polarized electromagnetic waves propagating with high n|| in the vicinity of the cyclotron resonance, what provides effective single-pass absorption of the injected microwave power.